Electrodeposited Trimetallic NiFeW Hydroxide Electrocatalysts for Efficient Water Oxidation. Issue 5 (21st January 2021) - Rajendiran, Rajmohan; Chinnadurai, Deviprasath; Chen, Kai; Selvaraj, Aravindha Raja; Prabakar, Kandasamy; Li, Oi Lun
Abstract: Tungsten‐doped Ni−Fe hydroxides fabricated on a three‐dimensional nickel foam through cathodic electrodeposition are proposed as effective oxygen evolution reaction (OER) catalysts for alkaline water oxidation. Incorporating an adequate amount of W into Ni−Fe hydroxides modulates the electronic structure by changing the local environment of Ni and Fe and create oxygen vacancies, resulting in abundant active sites for the OER. The optimized electrocatalyst, with a substantial number of catalytic sites, is found to outperform the well‐established 20 wt% Ir/C electrocatalyst. The catalyst only requires small overpotentials of 224 mV and 251 mV to generate current densities of 10 mA cm −2 and 50 mA cm −2, respectively, at an extremely low Tafel slope. Surface study after long‐term chronopotentiometry (ca. 30 h) reveals that the tungsten dopant undergoes reduction to stabilize the Ni and Fe active sites for predominant water oxidation. This research provides new insight to apply optimum amounts of tungsten doping to enable more significant electronic coupling within Ni−Fe for the chemisorption of hydroxy and oxygen intermediates and greatly improved OER activity. Abstract : W for the win : A low‐cost water oxidation electrocatalyst composed of W‐doped Ni−Fe hydroxides on Ni foam exhibits a low overpotential of 224 mV at 10 mA cm −2 at a small Tafel slope of 41 mV dec −1 with excellent durability. W doping leads an increased number of active sites and improved conductivity for superior OER performance in alkali media.